Abundance and survival rates of the Hawai'i Island associated spinner dolphin (Stenella longirostris) stock. - Julian A Tyne; Kenneth H Pollock; David W Johnston; Lars Bejder (PLoS ONE, 2014)
Reliable population estimates are critical to implement effective management strategies. The Hawai'i Island spinner dolphin (Stenella longirostris) is a genetically distinct stock that displays a rigid daily behavioural pattern, foraging offshore at night and resting in sheltered bays during the day. Consequently, they are exposed to frequent human interactions and disturbance. We estimated population parameters of this spinner dolphin stock using a systematic sampling design and capture-recapture models. From September 2010 to August 2011, boat-based photo-identification surveys were undertaken monthly over 132 days (>1,150 hours of effort; >100,000 dorsal fin images) in the four main resting bays along the Kona Coast, Hawai'i Island. All images were graded according to photographic quality and distinctiveness. Over 32,000 images were included in the analyses, from which 607 distinctive individuals were catalogued and 214 were highly distinctive. Two independent estimates of the proportion of highly distinctive individuals in the population were not significantly different (p = 0.68). Individual heterogeneity and time variation in capture probabilities were strongly indicated for these data; therefore capture-recapture models allowing for these variations were used. The estimated annual apparent survival rate (product of true survival and permanent emigration) was 0.97 SE ± 0.05. Open and closed capture-recapture models for the highly distinctive individuals photographed at least once each month produced similar abundance estimates. An estimate of 221 ± 4.3 SE highly distinctive spinner dolphins, resulted in a total abundance of 631 ± 60.1 SE, (95% CI 524-761) spinner dolphins in the Hawai'i Island stock, which is lower than previous estimates. When this abundance estimate is considered alongside the rigid daily behavioural pattern, genetic distinctiveness, and the ease of human access to spinner dolphins in their preferred resting habitats, this Hawai'i Island stock is likely more vulnerable to negative impacts from human disturbance than previously believed.